Challenging the supermarket giants : Sheng Siong's success and future plans. - Tan, Yi Lin. (2009)
This project is a case study analysis of Sheng Siong, a local chain of supermarkets in Singapore. The analysis involves the study of its success since the 2000s, with regards to its marketing mix as well as its segmentation, targeting and positioning strategies. It examines why and how they have been able to penetrate the industry despite the fierce competition, and also recommends possible plans for Sheng Siong to sustain its growth and success.